The Ethos of Noh: Actors and Their Art - Rath, Eric C. (Cambridge, MA Harvard University Press, 2004)
Since the inception of the noh drama six centuries ago, actors have resisted the notion that noh rests on natural talent alone. Correct performance, they claim, demands adherence to traditions. Yet what constitutes nohs traditions and who can claim authority over them have been in dispute throughout its history. This book traces how definitions of noh, both as an art and as a profession, have changed over time. The author seeks to show that the definition of noh as an art is inseparable from its definition as a profession.The aim of this book is to describe how memories of the past become traditions, as well as the role of these traditions in the institutional development of the noh theater from its beginnings in the fourteenth century through the late twentieth century. It focuses on the development of the key traditions that constitute the "ethos of noh," the ideology that empowered certain groups of actors at the expense of others, and how this ethos fostered nohs professionalization--its growth from a loose occupation into a closed, regulated vocation. The author argues that the traditions that form the ethos of noh, such as those surrounding masks and manuscripts, are the key traits that define it as an art.
Keywords: Theater history; Actor; Acting; Japan